Analisis Pemilihan Supplier Suku Cadang dengan Menggunakan Metode AHP dan TOPSIS di Perusahaan Forwarding - Arifin, Martin Marcelino; Vikaliana, Resista (Universitas Batanghari, 2024)
The forwarding company that will be studied is a subsidiary operating in the logistics services sector of a State-Owned Enterprise (BUMN) company that provides forwarding and warehousing services. The company has 30 trailer trucks in operation so it needs a competent spare parts supplier to meet the company's needs. Currently, companies only pay attention to price as the main factor in choosing suppliers, which ultimately causes late deliveries from these suppliers. In addition to looking for the best suppliers that companies should choose, this research aims to determine the main criteria and main sub-criteria for businesses in the process of selecting spare parts providers. In determining the weight of each criterion and ranking of suppliers that companies should prioritize, the TOPSIS approach and AHP method are used in this research. There are 5 criteria and 15 sub-criteria as well as 4 alternative suppliers that are compared. The supplier with the highest weight after using Expert Choice 11 software and the AHP technique is supplier 1 with a weight of 0.421, supplier 2 with a weight of 0.164, supplier 3 with a weight of 0.12, and supplier 4 with a weight of 0.294. By using the TOPSIS approach, supplier priority is obtained, namely supplier 1 has a preference value of 0.9256, supplier 4 has a value of 0.5217, supplier 2 has a value of 0.1829, and supplier 3 has a value of 0.0180.